EFFECT OF SERVICE QUALITY ON TAXPAYER SATISFACTION AT THE PRATAMA TAX SERVICE OFFICE, MEDAN TIMUR - Sharah Nofrissa Magdalena Simanjuntak; Rismayani Rismayani; Parapat Gultom (Cross-Border Journal of Business Management, 2022)
The purpose of this research is to find out and analyze the effect of service quality on taxpayer satisfaction at the Pratama Tax Service Office, Medan Timur. This type of research is descriptive quantitative and explanatory. The population in this study are all registered taxpayers in the service of individual taxpayers in 2014 amounting to 6,196 people. So the samples in this study are 99 samples. The data collection techniques use in this study are interviews, list of questions, and study documentation. The data analysis model use in this study is multiple regression analysis. The results of the research through the simultaneous test (F) show that physical evidence, reliability, responsiveness, assurance, and empathy have a significant effect on taxpayer satisfaction. The results of the partial test (t) show that physical evidence has a positive and significant effect on taxpayer satisfaction. Reliability has a positive and significant effect on taxpayer satisfaction. Responsiveness has a positive and significant effect on taxpayer satisfaction. Assurance has a positive and significant effect on taxpayer satisfaction. Empathy has a positive and significant effect on taxpayer satisfaction. The results of the coefficient of determination test (R2) show that physical evidence, reliability, responsiveness, assurance, and empathy can explain the variation of taxpayer satisfaction by 89.1% and the remaining 10.9% is influenced by other variables not examined.